Fucoidan alleviated colitis aggravated by fiber deficiency through protecting the gut barrier, suppressing the MAPK/NF-κB pathway, and modulating gut microbiota and metabolites - Zheng, Weiyun; Tang, Shuangru; Ren, Xiaomeng; Song, Shuang; Ai, Chunqing (Frontiers in Nutrition, 2025)
Insufficient dietary fiber intake has become a global public health issue, affecting the development and management of various diseases, including intestinal diseases and obesity. This study showed that dietary fiber deficiency enhanced the susceptibility of mice to colitis, which could be attributed to the disruption of the gut barrier integrity, activation of the NF-κB pathway, and oxidative stress. Undaria pinnatifida fucoidan (UPF) alleviated colitis symptoms in mice that fed with a fiber deficient diet (FD), characterized by increased weight gain and reduced disease activity index, liver and spleen indexes, and histological score. The protective effect of UPF against FD-exacerbated colitis can be attributed to the alleviation of oxidative stress, the preservation of the gut barrier integrity, and inhibition of the MAPK/NF-κB pathway. UPF ameliorated the gut microbiota composition, leading to increased microbiota richness, as well as increased levels of Muribaculaceae, Lactobacillaceae, and Bifidobacterium and reduced levels of Proteobacteria, Bacteroidetes, and Bacteroides. Metabolomics analysis revealed that UPF improved the profile of microbiota metabolites, with increased levels of carnitine and taurine and decreased levels of tyrosine and deoxycholic acid. This study suggests that UPF has the potential to be developed as a novel prebiotic agent to enhance human health.